Pengaruh Rasio Solvabilitas, Rasio Aktivitas, Dan Rasio Profitabilitas Terhadap Kinerja Keuangan (Studi Pada Perusahaan Ritel Yang Terdaftar Di Bursa Efek Indonesia Periode 2020-2022) - Yogy, Akhmad; Widarko, Agus; Primanto, Alfian Budi (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to determine the effect of Solvency Ratio, Activity Ratio, and Profitability Ratio on Financial Performance. This type of research is correlational with a quantitative approach. The population in this study were retail companies listed on the Indonesia Stock Exchange for the period 2020-2022. The sampling technique used purposive sampling with a sample of 10 companies. The data was obtained from the website www.idx.co.id. This research data analysis uses multiple linear regression analysis. This study contributes to understanding the factors that affect the financial performance of retail companies listed on the Indonesia Stock Exchange for the 2020-2022 Period. The results of this study are the Activity Ratio and Profitability Ratio have an effect on Financial Performance partially, while the Solvency Ratio has no partial effect. Simultaneously, the Solvency Ratio, Activity Ratio, and Profitability Ratio affect the Financial Performance of Retail Companies Listed on the Indonesia Stock Exchange for the 2020-2022 Period. Keywords: Financial Performance, Solvency Ratio, Activity Ratio, Profitability Ratio